2017
DOI: 10.1016/j.ijimpeng.2017.03.019
|View full text |Cite
|
Sign up to set email alerts
|

Experimental results and strength model identification of pure iridium

Abstract: This is a PDF file of an unedited manuscript that has been accepted for publication. As a service to our customers we are providing this early version of the manuscript. The manuscript will undergo copyediting, typesetting, and review of the resulting proof before it is published in its final form. Please note that during the production process errors may be discovered which could affect the content, and all legal disclaimers that apply to the journal pertain. Highlights  Mechanical characterization of pure i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 20 publications
(12 citation statements)
references
References 24 publications
0
12
0
Order By: Relevance
“…The availability of material strength models at high strain rates (most of them obtained experimentally by Hopkinson bar tests [4]) is limited to regimes of relatively low temperatures, well below the 2000°C reached in the core. A dedicated dynamic characterization of pure iridium at high temperatures by using Hopkinson bar tests was carried out to extract the material models necessary for this project [5]. However, the maximum temperature reached in these tests was only 1250°C.…”
Section: Introductionmentioning
confidence: 99%
“…The availability of material strength models at high strain rates (most of them obtained experimentally by Hopkinson bar tests [4]) is limited to regimes of relatively low temperatures, well below the 2000°C reached in the core. A dedicated dynamic characterization of pure iridium at high temperatures by using Hopkinson bar tests was carried out to extract the material models necessary for this project [5]. However, the maximum temperature reached in these tests was only 1250°C.…”
Section: Introductionmentioning
confidence: 99%
“…These numerical tools allow the implementation of advance material models, which take into account the material response beyond plastic deformation and even fracture. In this context, a dynamic characterization of Ir and W at high strain rates and temperatures was performed by means of Split‐Hopkinson Pressure bar tests . The parameters of the Johnson‐Cook strength model for these materials were extracted from these tests, to be used in the simulations.…”
Section: Previous Studies Leading To the Protad Designmentioning
confidence: 99%
“…In this context, a dynamic characterization of Ir and W at high strain rates and temperatures was performed by means of Split-Hopkinson Pressure bar tests. 6 The parameters of the Johnson-Cook strength model for these materials were extracted from these tests, to be used in the simulations. These numerical studies showed that a high-frequency radial mode is excited in the target core due to the sudden rise of temperature induced by each proton beam impact.…”
Section: Hydrocode Simulations Of the Dynamic Response Of The Targementioning
confidence: 99%
“…This study, published in ref. [67], included analysis of different modes of fracture of Ir, its dynamic behavior at high temperature and strain rates, and strength model extraction.…”
Section: Iridiummentioning
confidence: 99%
“…A series of tests from room temperature up to 1200 • C and at different strain-rates were performed at DYNLab in order to obtain information about temperature and strain-rate sensitivity of iridium. The strain-rate sensitivity was investigated starting from 10 −3 s −1 up to 10 4 s −1 [67]. The medium-low strain rate tests were performed using an electro-mechanical testing machine.…”
Section: Extraction Of J-c Parameters Of Iridium By Dynamic Testingmentioning
confidence: 99%